Analytical Modeling and Contradictions in Limestone Reservoirs: Breccias, Vugs, and Fractures. (28th April 2015) - Barros-Galvis, Nelson; Villaseñor, Pedro; Samaniego, Fernando
Abstract : Modeling of limestone reservoirs is traditionally developed applying tectonic fractures concepts or planar discontinuities and has been simulated dynamically without considering nonplanar discontinuities as sedimentary breccias, vugs, fault breccias, and impact breccias, assuming that all these nonplanar discontinuities are tectonic fractures, causing confusion and contradictions in reservoirs characterization. The differences in geometry and connectivity in each discontinuity affect fluid flow, generating the challenge to develop specific analytical models that describe quantitatively hydrodynamic behavior in breccias, vugs, and fractures, focusing on oil flow in limestone reservoirs. This paper demonstrates the differences between types of discontinuities that affect limestone reservoirs and recommends that all discontinuities should be included in simulation and static-dynamic characterization, because they impact fluid flow. To demonstrate these differences, different analytic models are developed. Findings of this work are based on observations of cores, outcrops, and tomography and are validated with field data. The explanations and mathematical modeling developed here could be used as diagnostic tools to predict fluid velocity and fluid flow in limestone reservoirs, improving the complex reservoirs static-dynamic characterization.